Dasar Pendidikan Agama Anak: Perspektif Nilai Sosial Budaya Masyarakat Aceh - Rahmi, Aulia; Chairullah, Chairullah; Fadhilah, Fadhilah (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2024)
Adat ngon hukom hanjet cree lage zat ngon sifet, meaning that Islamic law and customary traditions are inseparable, like essence and attribute. This Acehnese proverb reflects the deep interconnection between customary traditions (adat) and Islamic law (syara’). Without Islamic law, there would be no regulations for customs, and without customs, there would be no means to implement Islamic law. Consequently, Islam profoundly influences Acehnese culture, embedding Islamic values into most cultural practices. For instance, children are taught religious lessons from an early age, particularly about reading the Quran, performing prayers, moral conduct, and prohibitions according to tradition. Cultural traditions that embody child-rearing teachings include Peucicap, bringing children to religious teachers (teungku), circumcision ceremonies, Meudamee, peuayôn aneuk (putting children to sleep), mutual cooperation (gotong royong), Quran graduation ceremonies, and more.